A Secondary Mirror Alignment Method For Segmented Telescopes Using A Wavefront Sensor-less Method - Li, Min; Liu, Xin; Zhang, Ang; Zhang, Junbo; Xian, Hao (IEEE photonics technology letters, 2024)
The precise secondary mirror alignment is a key factor to ensure the imaging quality of a segmented telescope with a high resolution demand. In this paper, a two-step alignment method using an improved stochastic parallel gradient descent (SPGD) algorithm called Nadam SPGD algorithm is proposed. Simulation results show that our method can distinguish aberrations caused by phase errors of the primary mirror and position errors of the secondary mirror precisely, and align the secondary mirror quickly and accurately. The improved SPGD algorithm can enhance the correction efficiency by more than two times compared with the traditional SPGD algorithm.